Urgensi Lingkungan Sekolah Dalam Mewujudkan Children Well-Being Anak Usia Dini - Siti Nuramita; Taopik Rahman; Risbon Sianturi (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The school environment plays a strategic role in supporting children's well-being in early childhood, encompassing physical, social, emotional, and psychological aspects. This study aims to analyze the importance of the school environment in realizing early childhood well-being through a literature study approach. The method used is a literature study by reviewing various national and international journal articles published in the last ten years. The results of the study indicate that children's well-being is a multidimensional concept influenced by the interaction between children and their surroundings, including the school environment, which includes physical conditions, social interactions, and psychological climate. A positive and supportive school environment, such as a safe and comfortable learning space, warm relationships between teachers and children, and opportunities for play and exploration, has been shown to contribute to children's social-emotional development and happiness. In addition, children's well-being is also an important foundation for the success of the learning process, so that the school environment functions not only as a place of learning but also as a holistic growth space for early childhood. Thus, it can be concluded that the school environment has a high urgency in realizing children's well-being in early childhood. Therefore, optimal efforts are needed from educators and educational institutions to create a conducive, inclusive, and child-oriented environment